1989
DOI: 10.1164/ajrccm/140.3.706
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Relaxation Rate of Inspiratory Muscles in Patients with Sleep Apnea

Abstract: To evaluate whether inspiratory muscle function is impaired in patients with sleep apnea, we measured inspiratory muscle strength and relaxation rate before and after sleep in 13 patients. The sleep apnea group was composed of eight patients with severe obstructive sleep apnea, and the non-apnea group was composed of five patients without significant sleep apnea. We chose the time constant of relaxation (TauR) as an index of impaired inspiratory muscle contractility, and in subsets of each group, we measured t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 6 publications
1
19
0
Order By: Relevance
“…This finding appears to be at variance with the results of GRIGGS et al [11], who reported an increase in the τR of pleural pressure during voluntary sniff manoeuvres, measured prior to sleep and upon awakening in an apparently similar group of OSA patients. They found no change in maximal mouth pressures from night to morning.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…This finding appears to be at variance with the results of GRIGGS et al [11], who reported an increase in the τR of pleural pressure during voluntary sniff manoeuvres, measured prior to sleep and upon awakening in an apparently similar group of OSA patients. They found no change in maximal mouth pressures from night to morning.…”
Section: Discussionsupporting
confidence: 74%
“…They found no change in maximal mouth pressures from night to morning. The changes in τR were, therefore, interpreted as evidence of impaired inspiratory muscle contractility without development of overt fatigue [11]. Conceivably, their findings may have related to selective changes in contractility of nondiaphragmatic inspiratory muscles identified by assessment of τR using pleural pressure rather than Pdi [24].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Indeed, some investigators have hypothesised that respiratory muscle fatigue would occur in patients with severe OSA [22,23]. In keeping with this hypothesis, GRIGGS et al [22] reported a prolonged relaxation rate of inspiratory muscle in patients with sleep apnoea.…”
Section: Significance Of the Findingsmentioning
confidence: 93%
“…Indeed, some investigators have hypothesised that respiratory muscle fatigue would occur in patients with severe OSA [22,23]. In keeping with this hypothesis, GRIGGS et al [22] reported a prolonged relaxation rate of inspiratory muscle in patients with sleep apnoea. In contrast, MONTSERRAT et al [21] and CIBELLA et al [24], using the technique of diaphragm EMG frequency analysis, were unable arterial oxygen saturation (Sa,O2).…”
Section: Significance Of the Findingsmentioning
confidence: 93%